Information literacy and intention to adopt e-pharmacy: a study based on trust and the theory of reasoned action - Mingyue Fan; Oscar Chidiebere Ukaegbu (BMC, 2024)
Abstract Background E-pharmacy has gained popularity as an increasingly utilized platform for accessing healthcare services online. However, its adoption exhibits regional variations and necessitates improvement in certain aspects. Guided by the Theory of Reasoned Action (TRA) and Trust theory, this research explores the pivotal role of information literacy in influencing attitudes, perceived control, word of mouth, and trust. The overarching aim is to understand how these factors collectively impact the adoption of E-pharmacy services. Methods The study employed Structural Equation Modeling to assess data collected from 473 participants in Nigeria. This methodology allowed for a comprehensive evaluation of the intricate relationships between information literacy, attitudes, perceived control, word of mouth, trust, and E-pharmacy adoption. By utilizing statistical tests within this framework, the research sought to provide a robust analysis of the data and derive meaningful insights. Results The findings of the research underscore the significance of information literacy in shaping individuals' attitudes towards E-pharmacy. Higher information literacy levels were associated with more positive attitudes, an enhanced sense of perceived control, and increased positive word-of-mouth regarding the use of E-pharmacy services. Additionally, the study revealed that trust plays a crucial intermediary role between word-of-mouth communication and the actual adoption of E-pharmacy. Conclusions In summary, this research offers a novel and comprehensive explanation of the relationship between information literacy and the adoption of E-pharmacy services. The study's outcomes contribute valuable insights to the ongoing discourse on E-pharmacy adoption, emphasizing its potential to enhance healthcare accessibility and efficiency within the evolving landscape of digital healthcare. The implications of the findings extend to policymakers, healthcare providers, and other stakeholders interested in optimizing the adoption and integration of E-pharmacy services.